Evaluation of antioxidant capacity and flavor profile change of pomegranate wine during fermentation and aging process. (1st October 2017) - Lan, Yongli; Wu, Jin; Wang, Xuejiao; Sun, Xuchun; Hackman, Robert M.; Li, Zhixi; Feng, Xianchao
Highlights: Antioxidant activities of pomegranate wine are higher than red wines reported. Pomegranate wine can effectively scavenge both oxygen and nitrogenous radicals. Taste and aroma profiles of pomegranate wine were evaluated throughout brewing. Day 0–4 was the crucial period for characteristic flavor formation of wine. Major phenolic and volatile compounds in pomegranate wine were confirmed. Abstract: Antioxidant properties and flavor characteristic profile of pomegranate wine during winemaking were investigated. The total phenol content and radical scavenging activity exhibited a slightly decrease in the end edge. Punicalagins and gallic acid were revealed to be the most abundant phenolic compounds, followed by ellagic acid and vanillic acid. These constituents were mainly responsible for the effective antioxidant capacity of pomegranate wine. The major changes of flavor qualities occurred in the initial stage, particularly 0–4 day of fermentation. Fermentation significantly reduced the relative content of aldehydes, ketones, heterocyclic and aromatic compounds, but promoted the generation of esters and alcohols. This is the first time of using E-nose and E-tongue to monitor odour and taste changes in the brewing process of pomegranate wine. The study may provide a promising instruction for improving functional features and quality control of the pomegranate wine.